Fraxinus l. Species of Odessa region - Лотицький, Д. В. (Man and Environment. Issues of Neoecology)
A list of genus Fraxinus L. (ash) species of Odessa region was made. There are was found the representatives of three Fraxinus L. sections: Melioides (Endl.) Pfeiff., Fraxinus (DC.) V. Vassil., Ornus (Boehm.) DC. It was made a list of most common ash species of Odessa region: F. excelsior L., F. oxycarpa Willd., F. angustifolia Vahl., F. americana L., F. lanceolata Borkh., F. pennsylvanica Marsh. and species of urban, private and collectible plants: F. ornus L., F. monophilla Desfr., F. mandshurica Rupr., F. velutina Torr., F. pallisiae Willmott. There was found a list of species able to interbreed: F. excelsior L., F. oxycarpa Willd, F. angustifolia Vahl. and F. americana L., F. pennsylvanica Marsh., F. lanceolata Borkh. We make a hypothesis about the existence of hybridization zone of F. excelsior L., F. oxycarpa Willd., F. angustifolia Vahl. and F. americana L., F. lanceolata Borkh., F. pennsylvanica Marsh. through the North-Western Black Sea region and likely possibility perspective of native species displacement by invasive active American species, basing on analysis of data about ash species distribution in Eastern Europe flora.